Riskier Tests of the Validity of the Bifactor Model of Psychopathology. (November 2019) - Watts, Ashley L.; Poore, Holly E.; Waldman, Irwin D.
We advanced several "riskier tests" of the validity of bifactor models of psychopathology, which included that the general and specific psychopathology factors should be reliable and well represented by their respective indicators and that including a general factor should improve on the correlated factor model's external validity. We compared bifactor and correlated factors models of psychopathology using data from a community sample of youth ( N = 2, 498) whose parents provided ratings on psychopathology and theoretically relevant external criteria (i.e., personality, aggression, antisociality). Bifactor models tended to yield either general or specific factors that were unstable and difficult to interpret. The general factor appeared to reflect a differentially weighted amalgam of psychopathology rather than a liability for psychopathology broadly construed. With rare exceptions, bifactor models did not explain additional variance in first-order psychopathology symptom dimensions or external criteria compared with correlated factors models. Together, our findings call into question the validity of bifactor models of psychopathology and the p factor more broadly.